Auxin-regulated timing of transition from vegetative to reproductive growth in rapeseed (Brassica napus L.) under different nitrogen application rates - Hao, Pengfei; Lin, Baogang; Ren, Yun; Hu, Hao; Xue, Bowen; Huang, Lan; Hua, Shuijin (Frontiers in Plant Science, 2022)
Shoot apical meristem (SAM) differentiation is a key point to determine the change from vegetative to reproductive growth in rapeseed (Brassica napus L.). However, the regulation on SAM differentiation by nitrogen application through auxin biosynthesis and metabolism is largely unknown. In this research, the function and mechanisms of different nitrogen application rates (low N, N1; normal N, N2; high N, N3) on different FM development stages (T0, 5 d before N3 came into FMd; T1, N3 just came into FMd;T2, N2 entered into FMd; T3, N1 entered into FMd; T4, 5 d after N1 entered into FMd) were investigated. We found that the stage of FM differentiation, which was identified through stereomicroscope and scanning electron microscope, came 4 and 7 d earlier under high N level than under normal and low N levels, with the seed yield increased by 11.1% and 22.6%, respectively. IAA, as one of the most important phytohormones, the function of which was illustrated in the process of FM differentiation under different nitrogen levels. The dominated biosynthesis way of auxin was indole acetaldehyde oxime (IAOx) pathway, with 3-Indole acetonitrile dramatically accumulated during FM differentiation. At the same time, an obviously decrease of IAA contents at each FM differentiation stage were detected, then gradually rose up. To illustrate the mechanisms of auxin on FM differentiation under different N levels, the expression of genes involved in auxin biosynthesis, auxin signaling transduction and FM identify were performed at the 5 stages. Results showed that, genes involved in auxin biosynthesis were regulated before FMd, while the regulation of FM identity genes appeared mainly at the middle and later periods of the 5 stages, and the regulation level of genes varied under different N levels. In conclusion, high nitrogen level could accelerate the initiation of FMd, and auxin involved a lot in this regulation.